What Determines Private School Choice? A Comparison between the United Kingdom and Australia - Dearden, L; Sibieta, L; Ryan, C (My University, 2011)
The type of school a child attends is known to impact on educational attainment and laterlife outcomes. But there is very little persuasive empirical evidence—despite widespread and varied anecdotal evidence—on why parents opt to educate their children outside the state system. In this article, we seek to address this question by comparing the determinants of private school choice in both Australia and the United Kingdom. The experiences of the two countries have been very different over the recent past. Whilst private school attendance has remained largely flat in the United Kingdom at around 6–7 per cent of children, it has risen sharply in Australia, with about one third of children currently attending a school outside the government sector. Fully 20 per cent of Australian school children attend Catholic schools and about 13 per cent attend other nongovernment or independent schools. The levels of public subsidies are also very different in the two countries, with large public subsidies on offer inAustralia and no direct subsidy in the United Kingdom. Ryan and Sibieta (2011) describe the differences between private schooling in the United Kingdom and Australia in more detail
Keywords: Children -- School age; Children -- Outcomes; Childhood and child development; Children; School age; Outcomes; Childhood and child development